2017
DOI: 10.1039/c7cp02390a
|View full text |Cite
|
Sign up to set email alerts
|

First principles study of oxygen molecule interaction with the graphitic active sites of a boron-doped pyrolyzed Fe–N–C catalyst

Abstract: We study the adsorption and the dissociation of O molecules on the active sites of a boron-doped pyrolyzed Fe-N-C catalyst using density functional theory. Initially, we determine the possible structure of the FeN active site of the pyrolyzed Fe-N-C catalyst doped with a boron atom by considering the presence of a nitrogen atom as a metal-free site. The most stable configuration of the structure occurs when the boron and nitrogen atoms coalesce with the FeN site forming a complex site. This structure has highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 40 publications
3
37
0
Order By: Relevance
“…Structures with the lowest formation energy are those where the B atom is directly bound to the N atom of NiN 4 center, similar to what has been observed in the FeN 4 -G system. 36 We also find that BN substitution lowers the total energy of the system, indicated by a more negative formation energy compared to its corresponding undoped structure, as depicted in Figure 2. For instance, BN substitution on NiN 4 -G lowers the formation energy of the system by 1.25 eV.…”
Section: ■ Results and Discussionmentioning
confidence: 51%
See 3 more Smart Citations
“…Structures with the lowest formation energy are those where the B atom is directly bound to the N atom of NiN 4 center, similar to what has been observed in the FeN 4 -G system. 36 We also find that BN substitution lowers the total energy of the system, indicated by a more negative formation energy compared to its corresponding undoped structure, as depicted in Figure 2. For instance, BN substitution on NiN 4 -G lowers the formation energy of the system by 1.25 eV.…”
Section: ■ Results and Discussionmentioning
confidence: 51%
“…We used the previously obtained most stable structure of interior and edge NiN 4 sites to be doped with boron. In determining the position of boron defect, we followed the procedure outlined by Fajrial et al 36 The framework constitutes a stepwise approach of initially substituting a B atom, followed by a N atom. The procedure is reiterated in Section S3.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, they chose the most stable active site configuration, indicating that the active site could reduce the activation energy of oxygen dissociation with DFT calculations. In addition, Fajrial et al 23 reported that the dissociation of O 2 molecule on the boron‐doped FeNC catalyst through density functional theory (DFT). They found that the activation energy of O 2 dissociation on B‐doped FeNC catalyst is half of that on the un‐doped FeN 4 G.…”
Section: Introductionmentioning
confidence: 99%